1996
DOI: 10.12968/jowc.1996.5.5.213
|View full text |Cite
|
Sign up to set email alerts
|

Four-layer bandaging and healing rates of venous leg ulcers

Abstract: This paper reports the healing rates of venous leg ulcers in a community setting (Exeter and District Community Health Services NHS Trust) using the Charing Cross four-layer compression system. We report on 514 venous leg ulcers and show healing rates of 40% at 12 weeks, 50% at 17 weeks, 57% at 24 weeks and 80% predicted at 2 years. Patients were treated in one of 16 community leg ulcer clinics or in their homes. Nurses were allowed to use this system only after full training by the leg ulcer management serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 2 publications
2
22
0
Order By: Relevance
“…9 10 This probably reflects the larger areas and longer duration of ulcers at baseline in this trial. The nearest comparisons were described in two observational studies as 40% (of leg ulcers) in 12 weeks31 and 42% (of limbs) of people attending a leg ulcer clinic 32. The limitations for use of four layer bandaging in a community clinic include the fact that some people are unable to leave their home and cannot tolerate or do not like the treatment 33.…”
Section: Discussionmentioning
confidence: 99%
“…9 10 This probably reflects the larger areas and longer duration of ulcers at baseline in this trial. The nearest comparisons were described in two observational studies as 40% (of leg ulcers) in 12 weeks31 and 42% (of limbs) of people attending a leg ulcer clinic 32. The limitations for use of four layer bandaging in a community clinic include the fact that some people are unable to leave their home and cannot tolerate or do not like the treatment 33.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,17,19 This lead to the development of the 4-layer bandage (FLB) 18 that is widely used in community clinics in the United Kingdom. 1,2,4,5,20 The FLB system consists of an initial layer of orthopedic padding wool (Velband; Johnson & Johnson, Arlington, Tex; or Sofban; Smith & Nephew, Solothurn, Switzerland), a second layer of a short stretch bandage (Crepe); a third layer of a long stretch bandage (Elset, Seton, England), and a fourth layer of a cohesive middle stretch bandage (Coban; 3M, Rü schlikon, Switzerland). Modifications have been used for legs with a wide ankle size of 26 cm or larger and additional layers of orthopedic padding wool are advisable to protect the bony and tendinous prominences of legs with a small ankle size of 18-cm or less circumference.…”
Section: Studymentioning
confidence: 99%
“…In our opinion, data of the available literature are too divergent to decide if the healing rates are highest under the Unna boot with inelastic zinc plaster bandages, short stretch bandages, or long stretch bandages. [1][2][3][4][5] One systematic review of controlled trials on compression therapy of the legs found that elastic compression yields higher healing rates than inelastic compression therapy using zinc plaster. 6 Maybe one should start compression therapy of edematous legs with short stretch bandages that are to be renewed frequently (daily) and switch to medium and long stretch bandages that can be used for several days as soon as the leg is edema free.…”
Section: Importance Of Compression Therapy In General Dermatologymentioning
confidence: 99%
“…The four studies on compressive therapy with a descriptive-exploratory design proposed to: evaluate the relation between the pattern of venous incompetence and wound healing in patients using fourlayer compression bandages (24) ; determine the healing rate and cost of compression therapy (25) ; determine the healing rate with the use of the four-layer compression bandage system, Charing Cross (26) and evaluate the efficacy of the four-layer bandage system, Parema (27) . The study samples varied from 50 to 438 subjects and one counted 198 legs as a sample.…”
Section: Study Characterizationmentioning
confidence: 99%